PKCβII phosphorylates ACSL4 to amplify lipid peroxidation to induce ferroptosis - Zhang, Hai-Liang; Hu, Bing-Xin; Li, Zhi-Ling; Du, Tian; Shan, Jia-Lu; Ye, Zhi-Peng; Peng, Xiao-Dan; Li, Xuan; Huang, Yun; Zhu, Xian-Ying; Chen, Yu-Hong; Feng, Gong-Kan; et al. (Nature cell biology, 2022)
The accumulation of lipid peroxides is recognized as a determinant of the occurrence of ferroptosis. However, the sensors and amplifying process of lipid peroxidation linked to ferroptosis remain obscure. Here we identify PKCβII as a critical contributor of ferroptosis through independent genome-wide CRISPR–Cas9 and kinase inhibitor library screening. Our results show that PKCβII senses the initial lipid peroxides and amplifies lipid peroxidation linked to ferroptosis through phosphorylation and activation of ACSL4. Lipidomics analysis shows that activated ACSL4 catalyses polyunsaturated fatty acid-containing lipid biosynthesis and promotes the accumulation of lipid peroxidation products, leading to ferroptosis. Attenuation of the PKCβII–ACSL4 pathway effectively blocks ferroptosis in vitro and impairs ferroptosis-associated cancer immunotherapy in vivo. Our results identify PKCβII as a sensor of lipid peroxidation, and the lipid peroxidation–PKCβII–ACSL4 positive-feedback axis may provide potential targets for ferroptosis-associated disease treatment. Through CRISPR–Cas9 and kinase inhibitor screening, Zhang et al. show that PKCβII phosphorylates and activates ACSL4 to enhance polyunsaturated fatty acid-containing lipid biosynthesis, thereby promoting accumulation of lipid peroxidation and ferroptosis.